Reviving the Authority of Customary and Religious Institutions: Sustaining Post Conflict Peace in Mamasa, Indonesia - Mahyuddin, Mahyuddin; Nizah, Mohd Azmir; Mohad, Abd Hakim; Abd Rasyid (Jurnal Sosiologi Reflektif, 2026)
Post conflict societies face major challenges in rebuilding social unity, particularly in areas with long histories of communal and religious tension such as Mamasa, West Sulawesi. This study aims to analyze how customary authority and religious institutions interact with state institutions in sustaining post conflict peace in Mamasa. The research adopts a qualitative design using a case study approach. Data were collected through in depth semi structured interviews with ten purposively selected informants, including customary leaders, religious leaders, community members, youth figures, representatives of the Interfaith Harmony Forum (FKUB), and local government actors, supplemented by participant observation and an analysis of relevant policy documents. The data were analyzed thematically using an interpretative approach through coding, iterative theme development, and source triangulation. The findings indicate that sustainable peace in Mamasa is produced through a hybrid configuration that integrates the cultural legitimacy of customary institutions, the moral authority of religious actors, and the procedural support of state institutions in conflict resolution. The implication of this research is that strengthening institutional collaboration that connects restorative justice procedures with customary mediation and interfaith moral leadership is crucial for making reconciliation more durable.   Masyarakat pascakonflik menghadapi tantangan besar untuk membangun kembali kesatuan sosial, terutama di wilayah yang memiliki sejarah ketegangan komunal dan keagamaan seperti Mamasa, Sulawesi Barat. Penelitian ini bertujuan menganalisis bagaimana otoritas adat dan institusi keagamaan berinteraksi dengan institusi negara dalam mempertahankan perdamaian pascakonflik di Mamasa. Penelitian ini menggunakan desain kualitatif dengan pendekatan studi kasus. Penelitian ini menggunakan desain kualitatif dengan pendekatan studi kasus intrinsik. Data dikumpulkan melalui wawancara mendalam semi terstruktur dengan 10 informan yang dipilih secara purposif, yakni pemimpin adat, pemimpin agama, anggota masyarakat, tokoh pemuda, perwakilan FKUB, dan aktor pemerintah daerah, serta dilengkapi observasi partisipatif dan analisis dokumen kebijakan terkait. Data dianalisis secara tematik dengan pendekatan interpretatif melalui pengodean, pengembangan tema secara iteratif, dan triangulasi sumber. Hasil penelitian menunjukkan bahwa perdamaian berkelanjutan di Mamasa terbentuk melalui konfigurasi hibrida yang mengintegrasikan legitimasi budaya lembaga adat, otoritas moral aktor agama, dan dukungan prosedural institusi negara dalam resolusi konflik. Implikasi penelitian ini adalah pentingnya penguatan kolaborasi kelembagaan yang menghubungkan prosedur restorative justice dengan mediasi adat dan kepemimpinan moral lintas agama agar rekonsiliasi lebih tahan lama.